Guilty pleasures: Expenditure elasticities of ultra-processed foods and paid meals in India - Gupta, Manavi; Kishore, Avinash (International Food Policy Research Institute, 2025)
The rising consumption of ultra-processed foods (UPFs) and paid food away from home (FAFH) is a growing concern for developing countries like India, which face the double burden of persistent malnutrition and increasing obesity. This paper examines the trends and drivers of UPF and paid meal consumption in rural and urban India from 2014 to 2019. Using high-frequency household consumption survey data, we estimate the expenditure elasticity of these food categories. Our results show a significant increase in the consumption of UPFs and paid meals over the study period. The expenditure elasticity of both UPF and FAFH exceeds 1 on average, indicating that they are highly responsive to income growth. Notably, poorer and urban households display higher elasticities compared to wealthier and rural households. Oaxaca-Blinder decomposition reveals that rising incomes and evolving dietary preferences contribute to the increase in UPF and paid meal consumption. These findings underscore the need for targeted interventions to promote healthier food choices, especially among lower-income groups, as India's economy continues to grow.